A Regulated, Ubiquitin-Independent Degron in IκBα. Issue 17 (28th August 2015) - Fortmann, Karen T.; Lewis, Russell D.; Ngo, Kim A.; Fagerlund, Riku; Hoffmann, Alexander
Abstract: Whereas ubiquitin-dependent degrons have been characterized in some detail, how proteins may be targeted to ubiquitin-independent proteasomal degradation remains unclear. Here we show that IκBα contains an ubiquitin-independent degron whose activity is portable to heterologous proteins such as the globular protein GFP ( g reen f luorescent p rotein) via a proteasome-dependent, ubiquitin-independent, non-lysosomal pathway. The ubiquitin-independent degradation signal resides in an 11-amino-acid sequence, which is not only sufficient but also required for IκBα's short half-life. Finally, we show that this degron's activity is regulated by the interaction with NFκB, which controls its solvent exposure, and we demonstrate that this regulation of the degron's activity is critical for IκBα's signaling functions. Graphical abstract: Highlights: Uncomplexed IκBα has a short half-life due to ubiquitin-independent degradation. We show that IκBα contains a degron that can confer degradation of globular GFP. An 11-amino-acid sequence is sufficient and required for high turnover. The degron's activity is regulated by NFκB, which reduces its solvent exposure. Regulation of IκBα degron's activity is critical for proper NFκB signaling.